2005
DOI: 10.1007/s11269-005-0294-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of River Water Quality in Northwestern Greece

Abstract: The effect of land use patterns on river water quality was studied in three different river basins located in Epirus, Northwestern Greece. Studies were conducted from October 2000 to September 2001. During this period, the parameters chemical oxygen demand (COD), biological oxygen demand (BOD), NO − 2 , NO − 3 , NH + 4 and PO 3− 4 were measured, employing standard methods of analysis. The results were subjected to principal component analysis (PCA) for the estimation of the underlying variable correlations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 25 publications
0
42
0
4
Order By: Relevance
“…The results of hierarchical agglomerative CA can be presented in a dendrogram that visually describes the clustering course [27,28]. We employed hierarchical agglomerative CA to the normalized data to assemble monitoring sites and sampling months into aggregations using Ward's method, with squared Euclidean distances as a metric of similarity [29]. The hierarchical agglomerative CA was performed by the software IBM SPSS Statistics 20.…”
Section: Datamentioning
confidence: 99%
“…The results of hierarchical agglomerative CA can be presented in a dendrogram that visually describes the clustering course [27,28]. We employed hierarchical agglomerative CA to the normalized data to assemble monitoring sites and sampling months into aggregations using Ward's method, with squared Euclidean distances as a metric of similarity [29]. The hierarchical agglomerative CA was performed by the software IBM SPSS Statistics 20.…”
Section: Datamentioning
confidence: 99%
“…The application of different mathematical tools, such as principal component analysis (PCA) and cluster analysis (CA), allows the interpretation of complex data matrices to better understand the water quality and ecological status of the studied system (Kotti et al 2005;Koklu et al 2010;Ogleni and Topal 2011;Awadallah and Yousry 2012). These studies showed the ability of PCA and CA for the evaluation and interpretation of complex data sets to get better information about water quality and the design of the monitoring network for effective management of water resources.…”
Section: Introductionmentioning
confidence: 99%
“…al , Vončina, E. et. al 2007 as well as for river waters (Kotti, M. E. et. al 2005, Brodnjak-Vončina, D. et.…”
Section: Introductionmentioning
confidence: 99%